Avuncular Listening: The Unsuspected - Mowitt, John (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2009)
This essay approaches the topic of translation through the motif of “transmutation”, Roman Jakobson’s term for a modality of translation understood to be inter-semiotic as opposed to either intra or inter-linguistic. Instead of developing transmutation as a re-wording of “adaptation” (for example, the elaboration of a novel as the screenplay for a film), this text brings transmutation into contact with “remediation”, a concept used within media studies to describe how, as McLuhan famously put it, media are always comprised of other media. More specifically, and with an eye toward the particular tension between radio and film, this text shows how remediation repeats with a difference what Raymond Williams meant by “residualism”, the survival within the cultural dominant of politically charged cultural technologies and practices from an earlier moment. Key here is the rivalrous character of this tension, that is, the fact that media that include other media typically do so by subjecting them to their own formal and narrative logics. Here is explored this dynamic through a reading of Michael Curtiz’s The Unsuspected from 1947, a film that narrativizes the rivalry between radio and film.